Overlap syndrome with rowell's syndrome, antiphospholipid syndrome, primary sterility, and sensorineural hearing loss: A case report, brief review, and analysis of cases of rowell's syndrome reported from India and Abroad - Y K Sharma; Shivanti Chauhan (Wolters Kluwer Medknow Publications, 2018)
Rowell's syndrome (RS) is recognized since 1963 as a presentation of lupus erythematosus (LE) with erythema multiforme-like lesions and characteristic immunological changes. Antiphospholipid syndrome (APS) encompasses antibodies to phospholipids/phospholipid-binding cofactor proteins and/or circulating lupus anticoagulant with clinical manifestations of thrombosis such as recurrent spontaneous abortions, etc. A 32-year-old female with primary infertility since marriage (7 years) and sequential appearance, for the past 6 months, of various lupus-specific cutaneous lesions, "targetoid" lesions on palms, musculoskeletal, ocular and auditory (sensorineural hearing loss [SNHL]) complaints with positive serological profile for SMD-1, SS-A/Ro, SS-B/La, U1-snRNP, Ku, antiphospholipid and anticardiolipin antibodies, and histopathologically confirmed LE is presented as a case of concurrent overlap syndrome, RS and APS, primary infertility, and SNHL. A brief review of RS including analysis of data of cases reported from India hereto vis-a-vis that of cases worldwide up to 2012 has also been done.